In-Vitro Investigation of the Fracture Strength of Pulpotomized Primary Molars Restored with Glass Ionomer, Amalgam and Composite Resin with and without Cusp Reduction - Malekafzali, Beheshteh; Ghassemi, Amir; Mohtavipour, Saeedeh; Fotouhi Ardakani, Faezeh; Goodarzi, Niloofar; Fereydooni, Mahmood-Reza (Journal of Dental School, 2013)
Objective: Resistance to fracture is a critical issue when it comes to tooth restoration. The purpose of this study was to evaluate the fracture resistance of pulpotomized primary molars restored with glass ionomer (GI), amalgam and composite resin with and without cusp reduction. Methods: In this in-vitro experimental study, 60 extracted primary teeth were randomly divided into 6 groups of 10. In all groups except for the control group, conventional pulpotomy and MOD cavity preparation were performed in a way that the cavity isthmus width was equal to two-third of the inter cuspal distance. Group 1 teeth were restored with Kerr amalgam and underwent 1.5 mm cusp reduction, group 2 received Z250 composite resin onlay with 1.5 mm cuspal coverage, group 3 was restored similar to group 2 but without cusp reduction, group 4 was restored as group 3 but with Quixfil composite and group 5 was restored just like the former two groups but with GI. The restored teeth underwent thermocycling and were subjected to Universal Testing Machine with a crosshead speed of 0.5 mm/min. The recorded fracture resistance of specimens was compared. One- way ANOVA was used for statistical analysis. Results: The mean fracture resistance was 2001.929 in the control group, 904.749 in the amalgam group, 1101.736 in Z250 composite with no cusp reduction group, 1036.185 in the Quixfil composite with no cusp reduction, 945.096 in the Z250 composite with cusp reduction and 850.313 in the GI group. The difference between the control group and other understudy groups was statistically significant (p<0.0001) but other differences were not statistically meaningful. Conclusion: Although in none of the groups the fracture strength was equal to that of intact primary teeth, the obtained values were within the normal range of masticatory forces.